background image

Theorem 65

Let

(

A

;

Z

)

be a semifiltered down-aligned filtrator with finitely

meet-closed core

Z

which is a complete atomistic lattice and

A

is a distributive

lattice, then

Cor

(

a

A

b

) = Cor

a

Z

Cor

b

for every

a, b

A

.

Proof

Cor

(

a

A

b

) =

S

Z

x

|

x

is an atom of

Z

, x

a

A

b

 

(used proposi-

tion 34).

By the theorem 50 we have Cor

(

a

A

b

) =

S

Z

(atoms

A

(

a

A

b

)

Z

) =

S

Z

((atoms

A

a

atoms

A

b

)

Z

) =

S

Z

((atoms

A

a

Z

)

(atoms

A

b

Z

)) =

S

Z

(atoms

A

a

Z

)

Z

S

Z

(atoms

A

b

Z

) (used the theorem 1). Again using theo-

rem 50, we get Cor

(

a

A

b

) =

S

Z

{

x

|

x

is an atom of

Z

, x

a

}∪

Z

S

Z

{

x

|

x

is an atom of

Z

, x

b

}

=

Cor

a

Z

Cor

b

(again used proposition 34).

Theorem 66

Let

(

F

;

A

)

be a primary filtrator over a complete boolean lattice.

Then

(

a

F

b

)

+

=

a

+

A

b

+

for every

a, b

F

.

Proof

(

F

;

A

) is a filtered up-aligned complete lattice filtrator with finitely join-

closed (theorem 23) co-separable core (theorem 38) which is a complete boolean
lattice. Thus by the theorem 60

(

a

F

b

)

+

= Cor(

a

F

b

) = Cor

a

A

Cor

b

= Cor

a

A

Cor

b

=

a

+

A

b

+

.

Theorem 67

Let

(

A

;

Z

)

be a filtered distributive down-aligned, complete lattice

filtrator with finitely meet-closed, separable core which is a complete atomistic
boolean lattice. Then

(

a

A

b

)

=

a

Z

b

for every

a, b

A

.

Proof

(

a

A

b

)

= Cor

(

a

A

b

) = Cor

a

Z

Cor

b

= Cor

a

Z

Cor

b

=

a

Z

b

(used the theorem 61).

Theorem 68

Let

A

be a complete boolean lattice. Then

(

a

F

b

)

=

a

A

b

for every

a, b

F

.

Proof

(

F

;

A

) is a filtered complete lattice filtrator with down-aligned, up-

aligned, finitely meet-closed, separable core which is a complete boolean lattice.
So

(

a

F

b

)

= Cor(

a

F

b

) = Cor

a

A

Cor

b

= Cor

a

A

Cor

b

=

a

A

b

(used the theorem 61).

49